MENINGKATKAN KETERAMPILAN BERBICARA BAHASA INDONESIA MELALUI PEMBELAJARAN “BERGANTI PERAN” - Subakir (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
Unit Level Curriculum (SBC) suggested that the Indonesian language learning activities should be directed more towards activities that encourage students to learn actively, physically, socially and psychologically to understand the concept. Therefore, in the process of learning the Indonesian language using the methods teachers should make students do more activities realed to the learning process. With so many activities conducted, is expected to build a fun and enthusiasm learning process. Thus, understanding the concept, especially in terms of talk in the Indonesia language is getting better and learning outcomes also increased. This research aims to improve the ability to speak in class VII F SMP Negeri 1 Kalitengah using Role Reversal, with this method the student is given a group task, but individually still expected to be able to present the results of its work. This research was carried out in three cycles. With this strategy can increase their speaking skills. This is evident from the results of the evaluation (speech) made at the first cycle (66.86), second cycle (75.96), and the third cycle (81.14).